Caracterización de residuos sólidos urbanos de la ciudad de Chambo. - Ogoña Romero, Jefferson Andrés (2025)
The research focuses on characterizing municipal solid waste in the Chambo Canton. It is based on the book "Interdisciplinary Approach for the Sustainable Management of Drinking Water and Solid Waste in Ecuador" published by Arellano et al. 2024, which outlines various techniques and methodologies for determining urban and socioeconomic characteristics, per capita waste generation, physical composition, and waste density. In the urban area of Chambo, 133 residential blocks were quantified and categorized into three socioeconomic strata: B, C, and D. Stratum B accounts for 15.04% of the population and represents households with aboveaverage income; Stratum C, with 80.45%, includes households with below-average income; and stratum D, with 4.51%, includes low-income households. The sampling process was conducted in 81 randomly selected households over a period of seven consecutive days. The per capita waste generation was found to be 0.30 kg/person/day for Stratum B, 0.44 kg/person/day for stratum C, and 0.54 kg/person/day for stratum D, resulting in a weighted average of 0.42 kg/person/day. Regarding waste density, values obtained were 184.49 kg/m³ for stratum B, 204.06 kg/m³ for stratum C, and 200.69 kg/m³ for stratum D, resulting in a weighted average density of 200.96 kg/m³. In terms of physical composition, 68.40% corresponded to organic components, 20.61% to potentially recyclable materials, 0.5% to materials with future recycling potential, and 10.49% to non-recoverable waste. This information is essential for developing solid waste management plans in Chambo Canton.